The Glosten-Jagannathan-Runkle-Generalized Autoregressive Conditional Heteroscedastic Approach to Investigating the Foreign Exchange Forward Premium Volatility - Hamzaoui, Nessrine; Regaieg, Boutheina (International Journal of Economics and Financial Issues, 2016)
This paper empirically investigates the volatility dynamics of the EUR/USD forward premium via GARCH-M (1,1) and GJR-GARCH(1,1) and GJR-GARCH(1,1)-M models. Our empirical analysis is based on daily data related to the EUR/USD forward premiums. Our daily analysis reveals several results. Firstly, we confirm that the nine-month and one-year forward premiums are explained in large part by their conditional variances. Secondly, according to the theoretical predictions of the asymmetric framework, we show that the conditional variances equations exhibit an asymmetry in the dynamics of the conditional variance only for the 9 months and 12 months horizons. Thirdly, for the -6-month, 9-month and 12-month forward premiums; the GJR-GARCH in mean effect is totally absent. Keywords: Conditional volatility, GJR-GARCH, Generalized Autoregressive Conditional Heteroscedasticity, volatility persistence. JEL Classifications: C58, G14, G13, G15.